The viability of hydroponic agriculture in tropical developing regions: A case study of Nueva Ecija, Philippines - Edrian P, Macaso Mark (Asian Journal of Agriculture and Rural Development, 2025)
This case study examines the viability of hydroponic agriculture as a sustainable alternative to traditional farming in Nueva Ecija, Philippines, a tropical developing region facing rising production costs and climate change. It investigates the opportunities and challenges of adopting hydroponics in San Isidro, Lupao, and Bongabon, where pioneering farmers utilize this soilless cultivation. Data from early adopters, gathered via convenience sampling, offer insights into their management, technical adaptations, market access, and financial outcomes. The study analyzes hydroponics’ potential to enhance crop yields, reduce resource consumption (water, fertilizers, pesticides), and improve economic returns for smallholder farmers, aligning with Sustainable Development Goals. It also identifies barriers to wider adoption, such as initial investment and the need for specialized knowledge. Ultimately, this research aims to develop a strategic action plan to support the growth and sustainability of hydroponic agriculture in Nueva Ecija, providing a path for traditional farmers to overcome challenges and achieve greater productivity and profitability.